Improvement of Landrace Cultivars of Pearl Millet for Arid and Semi-Arid Environments - Bidinger, F R; Mahalakshmi, V; Talukdar, B S; Sharma, R K (Annals of Arid Zone, 2025)
Successful cultivars for arid and semi-arid environments combine adaptation to drought stress for dry years with a reasonable yield potential for better years. Improving the yield potential of adapted landrace cultivars may be the easiest way to achieve this combination for breeding programs with limited resources. This study, conducted with four adapted pearl millet landrace cultivars, compared the yield improvement from one cycle of St progeny plus mass reselection with that from topcrossnig the landraccs, on an early male-sterile line, with a good combinitig ability for grain yield. A single cyle of reselection increased mean yield of the landraces by 1190 over seven test environments, ranging in yield from 470 to 3010 kg ha-1. Topcrossing raised yields by an average of 32% over the same test environments. Topcrossing increased responsiveriess to improved environmental resources, as the advantage of the topcross hybrids over their parent landraces increased as environmental mean yield increased. Reselection, in contrast, increased mean yield but did not improve the response of the reselected cultivars to a changing environmental yield level.